Beyond Survival: How Adaptive Leadership and Knowledge Drive Entrepreneurial Breakthroughs in SMEs - Khurnia, Siti Lailatul; Pujianto, Wahyu Eko; Qurratu’aini, Nafia Ilhama; Kamila, Edita Rachma (Jurnal Entrepreneur dan Entrepreneurship, 2025)
National competitiveness is strongly impacted by economic development, which also heavily relies on the performance of entrepreneurs. The aim of this study is to investigate the relationship between entrepreneurial performance and knowledge competency and adaptive leadership. In this study, stakeholder pressure serves as a moderating variable. The sampling method used was purposive sampling. PLS-SEM was used to analyze the data from 203 SMEs’ owners, managers, shop heads, and decision-makers. The results showed that intellectual capacity and adaptable leadership significantly impacted entrepreneurial success. Furthermore, just as stakeholder pressure improves the relationship between knowledge competency and entrepreneurial performance, it also strengthens the relationship between adaptive leadership and entrepreneurial performance. However, it has no discernible effect. To achieve corporate sustainability, this study gives SMEs valuable insights on how to increase their knowledge capacity, adaptive leadership, and ability to respond to stakeholder demands.